Teacher educators' predictability and student selection paradigms in entrance examinations for the Finnish Primary School Teacher Education programme. Issue 2 (14th March 2020) - Mankki, Ville; Mäkinen, Marita; Räihä, Pekka
ABSTRACT: This article investigates the perceived and actual predictability of teacher educators working as assessors in entrance examinations for the Finnish Primary School Teacher Education (PSTE) programme. The section examining perceived predictability was conducted as a survey. The data for actual predictability, containing student teachers' entrance examination scores and student achievements, was collected from the student register. The findings indicate that although teacher educators consider themselves able to predict applicants' performance in the PSTE programme, their actual predictability in entrance examinations was poor. The assessments predicted only slightly student teachers' study pace in the PSTE programme, while better scores in entrance examinations predicted, in fact, weaker grades in studies. Teacher educators also conform to hidden quotas based on Finnish student selection paradigms in awarding better entrance examination scores to male and older applicants. The findings highlight teacher educators' need for more structured professional learning in a gatekeeping context.